A two-week running intervention reduces symptoms related to depression and increases hippocampal volume in young adults. (November 2021) - Fink, Andreas; Koschutnig, Karl; Zussner, Thomas; Perchtold-Stefan, Corinna M.; Rominger, Christian; Benedek, Mathias; Papousek, Ilona
Abstract: This study examined the effects of a two-week running intervention on depressive symptoms and structural changes of different subfields of the hippocampus in young adults from the general population. The intervention was realized in small groups of participants in a mostly forested area and was organized into seven units of about 60 min each. The study design included two intervention groups which were tested at three time points and which received the intervention time-delayed: The first group between the first and the second time point, and the second group between the second and the third time point (waiting control group). At each test session, magnetic resonance imaging (MRI) was performed and symptoms related to depression were measured by means of the Center for Epidemiological Studies Depression (CES-D) Scale. Results revealed a significant reduction of CES-D scores after the running intervention. The intervention also resulted in significant increases in the volume of the hippocampus, and reductions of CES-D scores right after the intervention were associated with increases in hippocampal volume. These findings add important new evidence on the beneficial role of aerobic exercise on depressive symptoms and related structural alterations of the hippocampus.